Abduil Majid. (2014). Peimbeilajaran Teimatik Teirpadui. Banduing: PT. Reimaja Rosda Karya. Auiliya Isti Makrifa. (2012). Eivaluiasi Tingkat Keilayakan Sarana dan Prasarana Ruiang Praktik Keilompok Keiahlian teiknik banguinan di SMK N 2 Yogyakarta seibaga - Fajar Budi Hermawan; Setuju; Sigit Purnomo (JURNAL VOKASI DEWANTARA (JVD), 2025)
This research aims to increase the activity and learning outcomes of class those in the class. The subjects of thisresearch were 34 class XII TKRO students. The research was carried out in two cycles and at the end of each cyclea reflection was carried out on the actions given. Data collection techniques in research use observation sheets, tests,project assignments and documentation. The research results show that the implementation of the Project BasedLearning learning model can increase the activity and learning outcomes in the PKKWU subject of class XII TKROIslamic Vocational School Sudirman Grabag Magelang students. This can be seen in the success of increasing studentactivity, in cycle I student activity was 71%, and increased in cycle II by 80%. Student learning outcomes in cycle Iaveraged 75, and increased in cycle II by 80. Thus, it is proven that the Project Based Learning learning model canincrease student activity and learning outcomes in PKKWU subjects.Keywords: Project Based Learning, Learning Activeness, Learning Results